Start-Up City Inspiring Private & Public Entrepreneurship, Getting Projects Done, and Having Fun - Klein, Gabe.; SpringerLink (Online service) (Washington, DC : Island Press/Center for Resource Economics : Imprint: Island Press, 2015)
In this publication, Gabe Klein, with David Vega-Barachowitz, demonstrates how to effect big, directional change in cities—and how to do it fast. Klein's objective is to inspire what he calls “public entrepreneurship,” a start-up-pace energy within the public sector, brought about by leveraging the immense resources at its disposal. Klein offers guidance for cutting through the morass, and a roadmap for getting real, meaningful projects done quickly and having fun while doing it. This book is for anyone who wants to change the way that we live in cities without waiting for the glacial pace of change in government.
Preface -- Introduction -- Why Should You Care about Getting Sh*t Done in Cities? -- 1. Lesson #1: Don’t Be Afraid to Screw Up and Learn -- 2: Lesson #2: Manage S.M.A.R.T -- 3. Lesson #3: Where There’s a Will, There’s a Way -- 4: Lesson #4: Sell Your City -- 5. Lesson #5: Fund Creatively -- 6: Lesson #6: Bridge the Public-Private Divide -- 7. Lesson #7: Prepare for Disruption -- 8. Lesson #8: Drive Change -- Conclusion: The Big Picture and You 209.
Keywords: Environment; Transportation; Environment, general; Transportation